On transformation formulas for theta hypergeometric functions - Denis, R.Y.; Singh, S.N.; Singh, S.P. (Український математичний журнал, 2012)
Using an identity and certain summation formulas for truncated theta hypergeometric series, we establish transformation formulas for finite bilateral theta hypergeometric series.